2015
DOI: 10.1186/s12906-015-0943-6
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhiza extract protects white matter and the hippocampus from damage induced by chronic cerebral hypoperfusion in rats

Abstract: BackgroundSalvia miltiorrhiza (SM), an herbal plant, is traditionally used in the treatment of cardiovascular and cerebrovascular diseases in Asian countries. SM has multiple biological effects including anti-inflammatory activity. The present study is aimed at investigating the effects of SM extract in rats with chronic cerebral hypoperfusion.MethodsChronic cerebral hypoperfusion was induced in male Wistar rats by permanent bilateral common carotid artery occlusion (BCCAo). The rats were divided into 3 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The bilateral common carotid artery occlusion (BCCAo) model, which is the most widely used VaD model, induces CCH by permanently ligating both common carotid arteries and shows pathological physiology similar to that in VaD patients [10,11,12,13]. We have investigated the therapeutic candidates, such as Fructus mume ( F. mume ), Ginkgo biloba L., Salvia miltiorrhiza , and cardiotonic pill, for CCH in the BCCAo model [14,15,16,17,18]. Notably, F. mume , a processed fruit of Prunus mume , improves BCCAo-induced cognitive impairment via the attenuation of the cholinergic system dysfunction and the inhibition of inflammation-related factors, such as gliosis, toll-like receptor-4 (TLR4), P38 mitogen-activated protein kinases (MAPK), and nuclear factor-κB (NF-κB) [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The bilateral common carotid artery occlusion (BCCAo) model, which is the most widely used VaD model, induces CCH by permanently ligating both common carotid arteries and shows pathological physiology similar to that in VaD patients [10,11,12,13]. We have investigated the therapeutic candidates, such as Fructus mume ( F. mume ), Ginkgo biloba L., Salvia miltiorrhiza , and cardiotonic pill, for CCH in the BCCAo model [14,15,16,17,18]. Notably, F. mume , a processed fruit of Prunus mume , improves BCCAo-induced cognitive impairment via the attenuation of the cholinergic system dysfunction and the inhibition of inflammation-related factors, such as gliosis, toll-like receptor-4 (TLR4), P38 mitogen-activated protein kinases (MAPK), and nuclear factor-κB (NF-κB) [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Chinese medicine is emerging as an attractive new generation of anticancer drugs due to their ability to effectively eliminate cancer cells with low toxicity (8)(9)(10). Salvia miltiorrhiza (Danshen), a popular Chinese herb, has been widely used for treating angina pectoris, myocardial infarction (MI) and stroke (11,12). Salvianolic acid B (Sal B) is one of the major water-soluble compounds and active ingredients of Danshen (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al showed that an intraperitoneal injection of S. miltiorrhiza extract at a dose of 5 mL/kg/day for 4 weeks could ameliorate the learning and memory decline of diabetic rats, as shown by the improved escape latency and platform-finding frequency in the Morris water maze test and the increased mitogen-activated protein kinase-1 (MKP-1) protein expression under the hyperglycemic condition [ 101 ]. According to Kim et al, the oral administration of S. miltiorrhiza extract could protect against the damage to the white matter and hippocampus in bilateral common carotid artery occlusion (BCCAo) rat model possibly via myeloid differentiation primary response 88 (MyD88)-dependent toll-like receptor 4 (TLR4) pathway [ 102 ]. S. miltiorrhiza extract administration at a dose of 200 mg/kg/day for 22 days attenuated the BCCAo-induced increase in TNF-α, IL-1β, IL-6, TLR4, and MyD88 and the decrease in myelin basic protein (MBP).…”
Section: Nervous System Diseasesmentioning
confidence: 99%